Pregnant Women's Knowledge about Bleeding and The Adherence to Antenatal Visits - Desmarnita, Ulty; Lolita, Noviola; Djuwitaningsih, Sri; Mulyanti, Yuli (Poltekkes Kemenkes Jakarta III, 2024)
Physiological and psychological changes during pregnancy can run normally if the mother is able to adapt to these changes. If there is a failure to adapt or there are other factors that affect the health of the mother during pregnancy, complications will arise. One of the abnormal complications during pregnancy is bleeding. To determine the relationship between the knowledge of pregnant women in the third trimester of signs of bleeding during pregnancy with compliance with antenatal visits at the Cipayung District Health Center, East Jakarta. Using a quantitative study with a cross sectional approach to 30 third trimester pregnant women with a purposive sampling technique. Data analysis using Chi-Square. The study was conducted in October-November 2020. The research instrument used a questionnaire made by the researcher about signs of bleeding during pregnancy. The results showed that the characteristics of the respondents were mostly aged 20-35 years (93.3%), primigravida (56.7%), secondary education (60%), less knowledgeable (60%), and obedient to antenatal visits (76.7%). The results of the bivariate analysis obtained p-value=1,000. There is no significant relationship between the knowledge of pregnant women in the third trimester of signs of bleeding during pregnancy and compliance with antenatal visits at the Cipayung District Health Center, East Jakarta. With this research, it is hoped that health workers, especially nursing staff, can provide information on the importance of adherence to antenatal visits to prevent risks for pregnant women, especially related to bleeding.